Solutions of Variational Inclusions over the Sets of Common Fixed Points in Banach Spaces - Salahuddin (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider two-step iteration methods to solve a variational inclusion problem over the set of common fixed points of an infinite family of nonexpansive mappings on real reflexive and strictly convex Banach space with a uniformly Gateaux differentiable norm.